A descriptive analysis of anglicism in ecuadorian magazines - Bermeo Villacis, Miriam de las Mercedes (2012)
The influence of the English language in Ecuador is well established due to the phenomena of immigration toward The United States of America, the globalization motivated by North American trading, and the progressive development of technology. Consequently, the presence of modern Anglicisms in Ecuadorian magazines is more prevalent than ever. This study, “A Descriptive Analysis of Anglicisms in Ecuadorian Magazines”, has the purpose of researching the phenomenon of Anglicisms used in Ecuadorian magazines since there are not any prior studies about this theme. This investigation was carried out in the city of Cuenca, Ecuador. The sample for this study was taken from six Ecuadorian magazines, two for each variable: Cultural: “Cuenca Ilustre” and “Vistal Sur”; scholarly: “America Economia” and “Coloquio”; general interest: “Mariela Viteri” and “Notas”. In order to carry out this project, I used the qualitative and quantitative methods. The linguistic analysis was made through the qualitative method which included a syntactic, semantic, and morphological analysis. The quantitative method was used for comparing the different variables based on frequencies and percentages in order to identify the most commonly used Anglicisms.